2013
DOI: 10.1179/1607845413y.0000000145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the correlations of hematological and biochemical variables with the stability of erythrocyte membrane in relation to sodium dodecyl sulfate

Abstract: The positive association between erythrocyte stability and RDW may reflect one possible mechanism involved in the clinical meaning of this hematological index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 42 publications
0
12
1
23
Order By: Relevance
“…Wider patient series with longer follow-up periods are needed to increase the reliability of RDW results. In recent studies, it was reported that there was a positive correlation between age and RDW (14,15). Although age was not taken into account in our study, no significant differences were identified between groups in terms of age.…”
Section: Discussioncontrasting
confidence: 50%
“…Wider patient series with longer follow-up periods are needed to increase the reliability of RDW results. In recent studies, it was reported that there was a positive correlation between age and RDW (14,15). Although age was not taken into account in our study, no significant differences were identified between groups in terms of age.…”
Section: Discussioncontrasting
confidence: 50%
“…À medida que a concentração salina no meio diminui, há um aumento gradativo da lise eritrocitária, que a partir de um determinado ponto sofre uma aceleração exponencial. Ao atingir o ponto intermediário da curva, a liberação de hemoglobina sofre uma desaceleração hiperbólica, até atingir um platô máximo estável (representado pela sigla A max ), que se refere ao valor estacionário máximo de absorvância de Freitas et al, 2014).…”
Section: Propriedades Da Membrana Eritrocitáriaunclassified
“…In this study, the possible association of alterations in erythrocyte behavior with PE will be investigated through the analysis of osmotic stability. The analysis of the erythrocyte behavior in an hyposmotic gradient is a powerful method that reflects the deformability [28], stability [29,30] and the membrane composition of these cells, allowing the investigation of the influences of the lipid blood levels [31] oxidative aggression [26], among other factors.…”
Section: Considerações Finaismentioning
confidence: 99%
See 2 more Smart Citations